2019
DOI: 10.1101/871137
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On the use of calcium deconvolution algorithms in practical contexts

Abstract: 1Calcium imaging is a powerful tool for capturing the simultaneous activity of large 2 populations of neurons. Here we determine the extent to which our inferences of neu-3 ral population activity, correlations, and coding depend on our choice of whether and 4 how we deconvolve the calcium time-series into spike-driven events. To this end, we 5 use a range of deconvolution algorithms to create nine versions of the same calcium 6 imaging data obtained from barrel cortex during a pole-detection task. Seeking sui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 58 publications
1
30
0
Order By: Relevance
“…Overall, applying FOOPSI to fluorescence traces led to a poorer recovery of ground truth 798 information using SMGM compared to direct application of SMGM to the florescence traces ( � ). This 799 finding is consistent with recent research that has questioned the accuracy of deconvolution methods 800 (Evans et al, 2019). We also tested other metrics to measure mutual information directly from the 801 fluorescence time traces (KSG, Binned Estimator (uniform bins), and Binned Estimator (occupancy 802 binned)) and found these alternatives produced highly variable, saturating measurements of recovered 803 versus ground truth information.…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Overall, applying FOOPSI to fluorescence traces led to a poorer recovery of ground truth 798 information using SMGM compared to direct application of SMGM to the florescence traces ( � ). This 799 finding is consistent with recent research that has questioned the accuracy of deconvolution methods 800 (Evans et al, 2019). We also tested other metrics to measure mutual information directly from the 801 fluorescence time traces (KSG, Binned Estimator (uniform bins), and Binned Estimator (occupancy 802 binned)) and found these alternatives produced highly variable, saturating measurements of recovered 803 versus ground truth information.…”
supporting
confidence: 80%
“…When applied to spiking data, there is also 119 a change in units: rather than action potential counts, functional fluorescence traces are typically plotted 120 in units of florescence change with respect to the baseline (ΔF/F). One possible solution to these issues 121 would be to deconvolve calcium traces to recover APs; however, deconvolution is an active area of 122 research, and the accuracy of these methods has recently been questioned (Evans et al, 2019). Ideally, the 123 calcium traces could be used directly to measure spiking information, without the need for such an in 124 between, potentially error introducing, step.…”
Section: Introduction 18mentioning
confidence: 99%
“…Quantitative inference of spike rates is critical for the analysis of existing and future calcium imaging datasets 4,5,21 . Although ΔF/F can in theory only report on spike rate changes, we found that absolute spike rates can be reliably inferred when the baseline activity is sufficiently sparse, which was the case in all datasets examined here (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, experimental conditions of novel datasets are often not well matched to those of available ground truth data. It is therefore not clear how an algorithm based on a specific ground truth dataset generalizes to other datasets, which causes problems for the inference of spike rates from calcium imaging data under most experimental conditions 12,13,20,21 .…”
Section: Introductionmentioning
confidence: 99%
“…We based our analyses of two-photon recordings on the fluorescence (ΔF/F0) time series rather than on activity reconstructed by deconvolution. The results of deconvolution methods can be highly sensitive to parameter choice, giving rise to variable conclusions as to neuronal response properties [109,110]. On the other hand, any analysis based on ΔF/F0 will overestimate neuronal correlations and give estimates on neuronal encoding of task variables that are likely to be a smoothed, filtered version of that occurring in reality [110,111].…”
Section: Experimental Considerationsmentioning
confidence: 99%